Design of A3B-Porphyrin Conjugates with Terpyridine as Potential Theranostic Agents: Synthesis, Complexation with Fe(III), Gd(III), and Photodynamic Activity - Kseniya A. Zhdanova; Anastasia V. Ivantsova; Fedor Yu. Vyalba; Maxim N. Usachev; Margarita A. Gradova; Oleg V. Gradov; Natalia Yu. Karpechenko; Natal'ya A. Bragina (MDPI AG, 2023)
This paper reports on the design and synthesis of new multifunctional porphyrin-based therapeutic agents for potential therapeutic and diagnostic applications. Zinc complexes of A3B-type meso-arylporphyrins containing OH- and COOH- groups were modified with chelating ligands based on 4'-(4-methylphenyl)-2,2':6',2"-terpyridine derivatives in high yields. Novel complexes with Gd(III), Fe(III) were obtained for these conjugates. Aggregation behaviour in solutions of different solubilisers was studied to inform the selection of the optimal solubilising platform for the porphyrins obtained; their photophysical and photochemical properties were also characterised. Micellar Pluronic F127 formulation was found to be the most effective solubiliser for stabilising the fluorescence-active monomolecular form of the photosensitisers (PS). In vitro cytotoxicity of the compounds was studied on the HEP-2 cell line with and without irradiation for 1.5 and 24 h. As a result, the IC50 of compounds 12 and 14 at an irradiation dose of 8.073 J/cm2 was shown to be 1.87 ± 0.333 and 1.4 ± 0.152 μM, respectively; without irradiation, the compound had no toxic effect within the studied concentration range (1.5 h). A test for the inhibition of metabolic cooperation or promoter activity was also performed for the abovementioned compounds, showing the efficacy and safety of the conjugates obtained. Preliminary data have indicated the high potential of the new type of PS to be promising molecular theranostic agents.